Effects of follicular output rate on cumulative clinical pregnancy rate and cumulative live birth rate in PCOS patients with different characteristics - Jiang, Rulan; Cao, Mingya; Hao, Haomeng; Jia, Rui; Chen, Peipei; Liu, Yuanyuan; Zhao, Zhiming (Frontiers in Endocrinology, 2022)
Aims: This study aims to explore the association between the follicular output rate (FORT) and cumulative ART outcomes in polycystic ovary syndrome (PCOS) patients with different characteristics undergoing in vitro fertilization (IVF) treatment. Methods: This was a retrospective study of 454 PCOS patients who underwent their first IVF cycle at our center from January 2016 to December 2020. FORT was calculated as pre-ovulatory follicle count (PFC)/antral follicle count (AFC) × 100. Multivariable regression analysis was performed to investigate the relationship between FORT and cumulative ART outcomes. Curve fitting and threshold effect analysis were established to find nonlinear relationships. Stratified analysis was performed to test for effect modification in subgroups. Results: According to the FORT, patients were divided into low, middle, and high FORT groups. Multivariable regression analysis showed that the FORT was an independent factor to significantly affect the cumulative clinical pregnancy rate (CCPR) and cumulative live birth rate (CLBR) (OR = 1.015, 95% CI: 1.001, 1.030 and OR = 1.010, 95% CI:1.001, 1.020). Curve fitting and threshold effect analysis showed that the CCPR and CLBR were positively associated with every percent increase of FORT when the FORT was less than 70% (OR = 1.039, 95% CI: 1.013, 1.065 and OR = 1.024, 95% CI: 1.004, 1.044). Stratified analysis showed that the CLBR increased by 1.3% with each additional unit of FORT for patients with hyperandrogenic manifestations (OR = 1.013, 95% CI: 1.001, 1.025). Compared with the low FORT group, in the high FORT group, CCPR increased 1.251 times for patients with polycystic ovarian morphology, while CCPR and CLBR increased 1.891 times and 0.99 times for those with ovulation disorder, respectively (OR = 2.251, 95% CI: 1.008，5.028 and OR = 2.891, 95% CI: 1.332, 6.323 and OR = 1.990, 95% CI: 1.133，3.494). Conclusion: In patients with PCOS, cumulative IVF outcomes have a positive correlation with FORT when the FORT was less than 70%. For PCOS patients with polycystic ovarian morphology, ovulation disorder or hyperandrogenic manifestations, a high FORT could be conductive to achieving better pregnancy outcomes.